Determination of fragrance allergens and their dermal sensitization quantitative risk assessment (QRA) in 107 spray perfumes. Issue 22 (17th November 2018) - Soo Lim, Duck; Min Choi, Seul; Kim, Kyu-Bong; Yoon, Kyungsil; Kacew, Sam; Sik Kim, Hyung; Lee, Byung-Mu
ABSTRACT: Cutaneous allergy occurs primarily as a result of using cosmetic, household, and laundry products available on the market that contain fragrances. The aim of this study was to develop a rapid and specific high-performance liquid chromatography with ultraviolet detection (HPLC-UV) method for quantification of 25 fragrance allergens (amyl cinnamyl alcohol, benzyl alcohol, benzyl benzoate, benzyl cinnamate, benzyl salicylate, citronellol, cinnamyl alcohol, citral, coumarin, eugenol, farnesol, geraniol, hydroxycitronellal, HICC (4-(4-hydroxy-4-methylpentyl)-3-cyclohexene-1-carboaldehyde), isoeugenol, isoeugenyl acetate, lilial (butyl phenyl methyl propional), limonene, linalool, methyl 2-octynoate, etc.). In addition, an exposure-based quantitative risk assessment (QRA) was performed to determine safe levels of fragrance ingredients in 107 perfumes. In 76 women's and 31 men's fragrances, 25 allergens were identified at concentrations ranging from undetectable (N.D.) to 8, 997.68 mg/kg, and from N.D. to 17, 352.34 mg/kg, respectively. An exposure-based sensitization QRA revealed that the ratios of acceptable exposure level (AEL) to consumer exposure level (CEL) of fragrance ingredients were greater than 1, suggesting an absence of skin sensitizing potential. However, the maximum level used in the exposure scenario was determined by the product purpose and application type, and AEL/CEL ratios of lilial, HICC, citral, isoeugenol, and methyl 2-octynoate analyzed in women's perfume were 0.53, 0.67 0.19, 0.13, and 0.57, respectively. As the ratios of AEL:CEL of these fragrance ingredients were below 1, the utilization of these potential skin sensitizers is not considered safe. Our findings indicate that the sensitization risk of allergens with AEL:CEL ratios below 1 detected in fragrances needs to be reduced to the appropriate human safety level for risk management.